DAMPAK LINGKUNGAN PELABUHAN PENYEBERANGAN ULEE LHEUE SETELAH PENGEMBANGAN TAHUN 2017 DAN SOLUSI PENGELOLAANNYA - Wien Linge; Azmeri Azmeri; Eldina Fatimah (Prodi Magister Teknik Sipil Unsyiah, 2019)
In overcoming the growing flow of passenger ship (ferry), a development at the Ulee Lheue ferry port has been carried out. This phase I development activities has been carried out, and has the potential to cause positive and negative impacts on the environment at the operational stage. This study aims to identify the environmental impacts of the Ulee Lheue ferry port after the 2017 development at the operational stage, and its management solutions, as well as identify the level of importance and satisfaction of passengers in the 2017 Ulee Lheue ferry port development activities. Lheue, Deah Geulumpang, Deah Baro and Alue Deah Teungoh. This research uses quantitative and qualitative methods. Environmental impacts in the operational phase that are reviewed are socio-economic aspects and socio-cultural aspects. Data processing consisted of validity and reliability tests, while the data analysis used descriptive analysis using Statistical Product and Service Solution (SPSS) software version 22, as well as biplot analysis using Minitab version 16 software. The results showed that the impact on socio-cultural aspects was labor recruited not from the local population, and conflicts between various drivers, while the impact on the socio-economic aspects was open business opportunities, increased economy of Banda Aceh City, open employment opportunities for security workers, and increased economy outside the City of Banda Aceh. The solution to managing the socio-cultural aspects is to add additional KP3 personnel, KP3 personnel are equipped with handy talky equipment, while the solution to the management of socio-economic aspects is priority placement for local workers according to educational qualifications, and priority placement for local people in business opportunities. An important development activity that is already satisfied is the building of sterile fences, an important but not satisfied development activity is the lobby building, and the development activities that are not important but not satisfied are the drop off buildings.